Impact of simulated acid rain on the composition of soil microbial communities and soil respiration in typical subtropical forests in Southwest China - Yifan Li; Yunqi Wang; Weiqiang Zhang (Ecotoxicology and Environmental Safety, 2021)
The relationship between soil respiration (SR) and microbial community structure (MCS) is relevant to changes in forest soil ecosystem stability and chemical cycling under acid rain. Simulated acid rain treatments of pH 4.5 (control), 4.0, 3.25 and 2.5 were applied to two forest stands in the Three Gorges Reservoir Area of Jinyun Mountain, Chongqing. We used phospholipid fatty acid (PLFA) analysis to observe the MCS in the 0–10 cm soil layer and measured SR in situ from January 2016 to December 2017. Additionally, we determined the effects of soil properties on the MCS and SR. Acid rain simulation significantly increased the fungal PLFA abundance and decreased the bacterial PLFA abundance in the mixed coniferous and broad-leaved forest (CF). However, in the evergreen broad-leaved forest (BF), the abundance of bacterial and fungal PLFAs did not differ significantly among treatments. Redundancy analysis (RDA) showed that significant changes in the MSC were mainly due to the C/N ratio, hydrolysable N content, content, fine root biomass and sucrase activity. Acid rain simulation in the CF and BF significantly inhibited SR, but the SR sensitivity to simulated acid rain differed among forests. In 2017, the annual mean SR in the CF under the pH 4.0, 3.25 and 2.5 treatments decreased significantly by 6.1%, 19.2% and 28.9%, but in the BF, SR decreased significantly by 25.6% only under pH 2.5. The structural equation model showed that the relationship between the MCS and the variation in SR was closer and more direct than that with soil nutrients. The microbial community structure was an important factor driving the response of soil respiration to acid rain.